2017
DOI: 10.21608/eajb.2017.12106
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Studies on Cotton Mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Sternorrhyncha: ‎ Coccoidea: Pseudococcidae) on Eggplant at ‎ Sharkia Governorate, Egypt

Abstract: Entomology Journal publishes original research papers and reviews from any entomological discipline or from directly allied fields in ecology, behavioral biology, Field experiments were conducted on cotton mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Sternorrhyncha: Coccoidea: Pseudococcidae) which infested eggplant at Hihhya distract, Sharkia Governorate during two successive seasons 2015 and 2016. The population density, activity periods, the effects of some weather factors, number of insect generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The theory suggests that the most appropriate host plant for a polyphagous insect pest should allow shorter APOP and TPOP and higher fecundity, net reproductive rate (R 0 ) and finite rate of increase (λ). Nabil [41] reported very high population densities of P. solenopsis in open field crops of eggplant in the Hihhya district, Sharqia Governorate in Egypt, reaching 328.75 individuals/leaf during September 2016. High densities of different instars of the pest reaching 150 individuals per plant were also recorded when reared on tomato in Israel by Spodek et al [11].…”
Section: Discussionmentioning
confidence: 99%
“…The theory suggests that the most appropriate host plant for a polyphagous insect pest should allow shorter APOP and TPOP and higher fecundity, net reproductive rate (R 0 ) and finite rate of increase (λ). Nabil [41] reported very high population densities of P. solenopsis in open field crops of eggplant in the Hihhya district, Sharqia Governorate in Egypt, reaching 328.75 individuals/leaf during September 2016. High densities of different instars of the pest reaching 150 individuals per plant were also recorded when reared on tomato in Israel by Spodek et al [11].…”
Section: Discussionmentioning
confidence: 99%
“…The above findings show that P. solenopsis favours the lower surface of the okra leaf over the upper surface. According to Nabil 14 and Mohamed 12 , they reported that the population of P. solenopsis was higher on the lower leaf surface than on the upper surface. This supports the theory that the distribution of mealybugs on the same plant is linked to the plant's age, the location of infestation, and the structural strength of the plant.…”
Section: 3-leaf Surfacementioning
confidence: 99%
“…From its recorded in Egypt in 2010 the pest was spreading rabidly infesting different host plants (Ibrahim et [25,8,6,9,15,33,11] . Accordingly, many studies were conducted on the Ecology, population density, dynamical fluctuations, associated natural enemies and biology of Phenacoccus solenopsis on many host plants (Nabil, 2017;Shehata, 2017;Nabil, and Hegab, 2019; Abd El-Mageed et al, 2020) [34,44,35,11] . Many control studies conducted to reduce its population by using natural and chemical compounds as well as measuring the effect of natural enemies to reduce the pest population level below the economic threshold (Mohyuddin et al 1997 [31,17,40,5,22,41,20] .…”
Section: Introductionmentioning
confidence: 99%